Immune defects in families and patients with xeroderma pigmentosum and trichothiodystrophy. - Mariani, E (1992)
Xeroderma pigmentosum (XP) is a rare autosomal recessive disease characterized by photosensitivity, a high incidence of cancer in sun-exposed portions of the skin and a reduced capacity to repair the u.v.-induced DNA damage. One of the XP mutations (XP-D) has also been identified in patients affected by trichothiodystrophy (TTD), a rare autosomal recessive disease characterized by brittle hair, mental and physical retardation, peculiar face and ichthyosis. However, in these patients there is no evidence of increased skin tumour incidence. Since an impairment of cell-mediated immunity has been proposed as a co-factor in the cancer proneness of XP patients, we investigated the involvement of immune defect(s) in five XP patients, five TTD patients, their parents, and 24 TTD relatives. We evaluated the phenotype of circulating lymphocytes, natural killer (NK) cell lytic activity, target cell binding of NK cells at single cell level and the effect of interferons (IFN) alpha and beta on NK cell activity. The relative proportion of CD3+ and CD4+ circulating lymphocytes was reduced in XP but not in TTD patients. NK cell lytic activity was decreased in XP patients and their mothers, but their fathers showed normal lytic activity. NK activity varied among TTD families: four out of five patients and their relatives presented low NK cell activity, and one family was normal. In TTD family members, NK activity increased after incubation with IFN-alpha or IFN-beta, but never reached normal values. In contrast, in XP patients and their mothers, the defect was almost completely corrected after in vitro incubation with IFN-alpha or IFN-beta. Our study indicates impaired NK lytic activity in the majority of TTD and XP patients and that this defect is present also in members of their families. In addition, XP patients present a low number of circulating T cells. These multiple abnormalities, together with DNA repair defects, could be related to the increased cancer risk in XP patients.